Effect of New Bobath Technology Combined with Intelligent Motion Feedback Training on Hand Function of Stroke Patients with Hemiplegia - Jie CHEN; Fuchun WU; Guoqing MO; Debiao YU (康复学报)
Objective:To observe the effect of new Bobath technology combined with intelligent motion feedback training on hand function of stroke patients with hemiplegia.Methods:A total of 68 stroke patients with hemiplegia were randomly divided into control group and treatment group, with 34 cases in each group. The control group was treated with routine rehabilitation therapy and occupational therapy, while the treatment group was treated with new Bobath technique and ntelligent motion feedback training on the basis of the control group.FMA-UE score of wrist motor function, MBI score of daily living ability and maximum activity of wrist joint dorsal extension on hemiplegic side were compared between the two groups.Results:After treatment for two, four and six weeks, the FMA-UE, MBI score and wrist dorsal extension maximum activity of the two groups improved significantly than those of treatment before, with statistically significant differences (P<0.05); After treatment for four and six weeks, the FMA-UE score and wrist dorsal extension maximum activity of the treatment group were significantly better than those of the control group, with statistically significant differences (P<0.05);after treatment for six weeks, MBI score of the treatment group was significantly better than that of the control group, with statistically significant differences (P<0.05).Conclusion:New Bobath technology combined with ntelligent motion feedback training can effectively improve hand function and self-care ability of stroke patients with hemiplegia.